Efektivitas Konseling Keluarga dalam Menangani Konflik Orang Tua dan Anak: Tinjauan Literatur Sistematis - Desta Reinita; Muhammad Ilham Bayu Dirgantara; Aria Aria; Muhammad Dicky; Putri Nur Hapsari; Nurhadia Nurhadia; Heldy Ferdian; Sepialdo Surya Pranata; Angga Septian Budi Saputra; Bachtiar Safrudin; Kartika Setia Purdani (El-Mujtama: Jurnal Pengabdian Masyarakat, 2026)
Family conflict between parents and children remains a prevalent psychosocial issue that can adversely affect emotional well-being, communication patterns, and overall family functioning. In recent years, family counseling has been increasingly utilized as an evidence-based intervention to address such conflicts; however, empirical findings continue to demonstrate variability depending on contextual and methodological factors. This study aims to systematically review the effectiveness of family counseling in managing parent–child conflicts based on recent empirical journal publications. The study employed a Systematic Literature Review (SLR) method by analyzing ten peer-reviewed journal articles published between 2020 and 2025. Articles were retrieved from reputable academic databases and selected using inclusion and exclusion criteria focusing on intervention models, research designs, and reported outcomes. The findings indicate that family counseling is consistently effective in reducing conflict intensity, improving communication quality, strengthening emotional bonds, and enhancing problem-solving capacities between parents and children. Various counseling approaches, including systemic family therapy, cognitive-behavioral family counseling, and solution-focused counseling, demonstrate positive outcomes when applied in accordance with family context and relational dynamics. Overall, the review confirms that family counseling constitutes a relevant and effective intervention for resolving parent–child conflicts. Future research is recommended to employ longitudinal designs and culturally responsive counseling frameworks to further strengthen the empirical evidence base.